Pengembangan Buku Ajar Akidah Akhlak Berbasis E-Book Story untuk Peningkatan Moral Reasoning Siswa - Mir’atus Sa’diyah; Esa Nur Faizah (Journal of Education and Learning Sciences, 2026)
Advancements in educational technology have increased demand for innovative digital learning materials that enhance conceptual understanding and foster students' moral reasoning. This study aimed to develop a "Story E-Book" for the Akidah Akhlak (Islamic Creed and Ethics) subject, specifically addressing stinginess and ingratitude for blessings, to improve the moral reasoning of fourth-grade students at a Madrasah Ibtidaiyah (Islamic elementary school). The study employed the Research and Development (R&D) method using the ADDIE model, comprising analysis, design, development, implementation, and evaluation. Product feasibility was validated by subject-matter, media, and instructional experts, while its effectiveness was tested using a one-group pretest-posttest design with 17 students, employing instruments based on moral reasoning indicators. Data were analyzed descriptively and through the N-Gain test. The results indicate that the Story E-Book was rated highly feasible by experts and effective in enhancing students' moral reasoning, demonstrating a high level of improvement. These findings suggest that integrating digital storytelling, interactive multimedia, and reflective activities can create a more meaningful learning experience while supporting character development within Akidah Akhlak instruction